Examining the impact of emotional intelligence and goal setting on basketball performance - Gill, G. S. (The Sport Journal, 2016)
The purpose of this investigation was to examine the impact of emotional intelligence and goal setting in basketball. Having acknowledged the importance of emotional regulation in performance a suitable intervention to facilitate this process was tested. Using quantitative analysis to measure performance, participants completed a goal setting and emotional intelligence questionnaire during three periods of the regular season. Results revealed that participants who displayed high emotional intelligence levels set frequent goals. Participants also found that barriers to goals were overcome through specific action planning and related to individual requirements. Data for emotional intelligence demonstrated that participants also became self-aware of their own performance levels. In sum, this investigation advocates the use of goal setting to enhance emotional intelligence levels for performance outcomes in basketball. Future research should engage the use of emotional intelligence with packaged mental skills (e.g. imagery, self-talk and relaxation) to enhance performance levels. Further, using regression analysis would be useful in examining relationships more closely with the inclusion of more qualitative methodology.